2021
DOI: 10.14245/ns.2142390.195
|View full text |Cite
|
Sign up to set email alerts
|

Indications for Nonsurgical Treatment of Thoracolumbar Spine Fractures: WFNS Spine Committee Recommendations

Abstract: Thoracolumbar spine is the most injured spinal region in blunt trauma. Literature on the indications for nonoperative treatment of thoracolumbar fractures is conflicting. The purpose of this systematic review is to clarify the indications for nonsurgical treatment of thoracolumbar fractures. We conducted a systematic literature search between 2010 to 2020 on PubMed/MEDLINE, and Cochrane Central. Up-to-date literature on the indications for nonoperative treatment of thoracolumbar fractures was reviewed to reach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 68 publications
(114 reference statements)
0
6
0
1
Order By: Relevance
“…[4][5][6] On one hand, some have argued that there are equivalent functional outcomes between operative and non-operative treatment thereby inherently favoring the avoidance of surgical management and its attendant complications. [7][8][9] On the other hand, surgical stabilization affords immediate surgical correction of spine alignment and obviates the purported delayed risks of post-traumatic deformity. 10,11 Gertzbein et al argued there was a clear improvement between the degree of kyphotic deformity and subsequent functional outcomes with surgical stabilization and this was shown with good effect by Schnake et al 12,13 However, Thomas et al found that there was no clear link between posttraumatic kyphosis and clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] On one hand, some have argued that there are equivalent functional outcomes between operative and non-operative treatment thereby inherently favoring the avoidance of surgical management and its attendant complications. [7][8][9] On the other hand, surgical stabilization affords immediate surgical correction of spine alignment and obviates the purported delayed risks of post-traumatic deformity. 10,11 Gertzbein et al argued there was a clear improvement between the degree of kyphotic deformity and subsequent functional outcomes with surgical stabilization and this was shown with good effect by Schnake et al 12,13 However, Thomas et al found that there was no clear link between posttraumatic kyphosis and clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Thoracolumbar fractures account for more than 50% of all spinal fractures (1), and pose a huge economic burden to the society and families. Patients with stable spine fractures can be treated conservatively, while surgery is needed for severe damage of the vertebral column, kyphotic deformity, or neurological disorders (2). At present, operative indications of type A thoracolumbar fracture without neurologic deficit include: (1) kyphotic deformity > 15-20°( compared with normal angle); (2) the loss of vertebral body height > 50%.…”
Section: Introductionmentioning
confidence: 99%
“…1 Anatomically and functionally thoracolumbar spine is divided into regid thoracic spine (T1-10), transitional thoracolumbar junction (T10-L2), and Flexible lumbar spine (L3-L5). 2 Thoracic spine being regid needs greater amount of force to produce fracture or dislocations, also narrow spinal canal at this region leads to high incidence of spinal cord involvement. 1 Lumbar spine being flexible with greater diameter of canal predisposing it to lesser incidence of neurological injuries.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Thoracolumbar spine fractures account for 90% of all spine fractures recorded. 2 Such injuries are very common among young people, between 20 and 40 years old, and the most common causes of such spine trauma are motor vehicle accidents, falls, and gunshot injuries. 7 The probability of developing a neurological deficit will depend on the type of fracture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation